Associated risk factors with incidence of irritant contact dermatitis among the cleaning worker in Santa Elisabeth Medan Hospital - Panjaitan, Joice Sonya Gani; Nababan, Donal; Tarigan, Frida Lina; Hidayat, Wisnu; Sitorus, Mido Ester J. (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Occupational irritant contact dermatitis (ICD) accounts for approximately 20% of work-related skin diseases, with 80% of cases affecting the hands. Cleaning staff are particularly susceptible to ICD. This study aimed to identify risk factors for ICD among cleaning staff at Santa Elisabeth Medan Hospital. A cross-sectional observational study was conducted involving 60 cleaning staff (total population) at the hospital in October-November 2023. The study investigated three groups of factors: host factors (age, gender, work duration, work stress, and personal protective equipment (PPE) use), agent factors (type of cleaning solution, duration and frequency of use), and environmental factors (perceived organizational support). The results showed that 8 of 60 cleaning staff (13.3%) had ICD. Statistical analysis revealed no significant association between ICD and host, agent, or environmental factors among cleaning staff (p > 0.05). Host, agent, and environmental factors were not found to be significant risk factors for OICD among cleaning workers at Santa Elisabeth Medan Hospital.